"At Least They're Workin' on My Case?" Victim Notification in Sexual Assault "Cold" Cases. Issue 9 (May 2021) - Sulley, Caitlin; Wood, Leila; Cook Heffron, Laurie; Westbrook, Lynn; Levy, Nicole; Donde, Sapana D.; Busch-Armendariz, Noël
Sexual assault is a significantly under-reported, -investigated, and -prosecuted crime in the United States, which criminal justice and advocacy actors across the country are working to address. Law enforcement procedures often involve providing crime victims, including sexual assault victims, with written notification by mail about the status of their case, but little is known about the best practices for victim notification in sexual assault "cold" cases. This qualitative research explored whether this standard law enforcement practice was appropriate for sexual assault victims in "cold cases" particularly when there had been no contact from law enforcement, despite forensic evidence having been tested. The research questions were what do sexual assault victims in cold cases have to say about victim notification protocols and practices? and What do sexual assault victims in cold cases have to say about hypothetical written victim notification protocols? Twenty-three sexual assault victims were asked in focus groups and individual interviews to respond to hypothetical written notification letters for content and the sending authority and to give input on alternative modes of communication. The data were analyzed using grounded theory. Themes related to trust, personal agency, and decision making from notification examples emerged. Recommendations on notification included respecting privacy, including specifics, identifying next steps, normalizing, translating, and providing resources. Implications for developing notification protocols include use of emerging evidence about neurobiology of trauma, use of victim input, and patience for the varying reactions and needs of sexual assault victims.